Long‐Term Outcomes of a Remedial Education Program for Doctors With Clinical Performance Deficits. Issue 2 (April 2014) - Lillis, Steven; Takai, Nikita; Francis, Sidonie
<x xml:space="preserve">Abstract</x> Introduction Medical regulatory authorities need reliable methods of assessing and remediating doctors where there are concerns over competence. There's a small but growing literature describing remediation programs and documenting their effectiveness. This article adds to that literature by describing a program associated with the Medical Council of New Zealand (MCNZ) and reporting outcomes for 24 consecutive doctors required to undergo remediation. Methods Over the 18‐month period covered in this study, 24 doctors were required by the MCNZ to enter remediation after a performance assessment. The data set used in this study was drawn from these 24 consecutive cases and included the nature of concerns, severity of concerns, results of remediation and outcome of a second assessment when such an assessment was ordered. Results Of 24 doctors who underwent initial assessment, 5 failed to engage with remediation and withdrew from clinical work. A 12‐month education remediation program was completed by all remaining 19 doctors. Of these, 13 were considered to be practicing at an acceptable standard at the end of remediation on the basis of sequential supervisor reports. Six doctors were required to have a second performance assessment. Of these, only 1 was considered to be functioning at an acceptable standard. Concurrent health concerns were common among this cohort of doctors. Discussion Seventy‐five percent of doctors who entered remedial education were considered to be practicing at an acceptable standard at the end of remediation. This accords well with international data. A small number of doctors appear to be unresponsive to remediation.